G110 The validity of standardised two-year neurodevelopmental status assessed during routine nhs follow-up of children born <30 weeks' gestation. (27th April 2015) - Wong, HS; Cowan, FM; Modi, N
Abstract : Aim: To determine the validity of standardised, routinely recorded NHS assessments in identifying neurodevelopmental impairments at age two years in children born <30 weeks' gestation. Methods: Children born <30 weeks' gestation, attending a routine NHS follow-up assessment at age 20–28 months from term, in 13 participating hospitals were invited to join the study. Data on neurodevelopmental outcome were recorded in a standardised format developed by the Thames Regional Perinatal Outcomes Group and entered into the electronic clinical record on the Badgernet platform. Data were extracted quarterly and held in the National Neonatal Research Database at the Neonatal Data Analysis Unit. Based on a predefined algorithm, each participant was classified as having 'no', 'mild-moderate' or 'severe' neurodevelopmental impairment in cognitive, language and motor domains. Participants also received a formal neurodevelopmental assessment conducted to research standards by a single assessor using the 3rd edition of the Bayley Scales (Bayley-III). The sensitivity and specificity of NHS assessments in identifying children with any impairment (Bayley-III scores <85) or severe impairment (Bayley-III scores <70) in each of the 3 domains were calculated. Results: One hundred and ninety children born at a median (IQR) gestational age of 27 (26–29) weeks participated. The validity of routine assessment in identifying children with no impairment was high across all domains (specificities 83.9–100.0% for no impairment; 96.6–100.0% for no severe impairment). The sensitivity of routine assessment in identifying gross motor impairment was also high, particularly for severe impairment. However, the identification of cognitive impairments (sensitivities (95% CI) were 69.7% (55.1–84.3%) for any impairment; 28.6% (5.0–52.2%) for severe impairment) and language impairment (53.2% (42.0–64.5%) for any impairment; 42.9% (14.2–71.5%) for severe impairment) were poor. Conclusions: Routine NHS assessments identify children with severe motor impairment with good specificity but lack adequate sensitivity in cognitive and language domains, areas where early intervention improves educational and social outcomes. About 7000 children are born ≤30 weeks' gestation each year in the UK. This study emphasised that follow-up assessments should performed by appropriately trained personnel using sensitive and specific standardised tests in order to achieve effective neurodevelopmental surveillance of this vulnerable population.